Insufisiensi Adrenal Tersier pada Penggunaan Steroid Jangka Panjang - Ni Kadek Ariesta Dwijayanthi; Wira Gotera (MEDICINUS, 2026)
Adrenal insufficiency is a life-threatening condition that may occur as a tertiary effect of long-term use of steroids. Steroid use in patients with gout arthritis is often administered chronically. However, without adequate medical supervision, it can cause a pathogenic loop of adrenal insufficiency through disruption of the cortisol negative feedback mechanism on the hypothalamic-pituitary-adrenal axis. This disruption leads to an inadequate cortisol response, allowing clinical symptoms of adrenal insufficiency to develop, and a fatal adrenal crisis could emerge. In this case, we reported a productive-aged man with underlying disease of gout arthritis who developed adrenal insufficiency. The patient presented with cushingoid clinical features and a secondary immunodeficiency state, with suspected adrenal crisis. Management of the acute condition was carried out, although the diagnostic confirmation of low plasma cortisol levels was only obtained after the patient had been discharged from the hospital. The innapropriate and unsupervised use of steroid remains a medical problem in our society. Inadequate screening related to this issue is still an unmeet obstacle. Early recognition of the clinical signs and symptoms of steroid-induced adrenal insufficiency is essential to ensure timely and appropriate management.